PENGARUH FASILITAS KERJA, PENGARAHAN, KOORDINASI DAN EVALUASI KINERJA TERHADAP KINERJA PEGAWAI DINAS KEHUTANAN PROVINSI SUM-SEL UPTD KPH UNIT XI KIKIM PASEMA LAHAT - FITRIADI ADI; HARDIANSYAH; NISMA APRIANI (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study to be achieved by the author is to determine, analyze and prove the effect of work facilities, direction, coordination and performance evaluation either partially or simultaneously on the performance of the employees of the South Sumatra Provincial Forestry Service UPTD KPH Unit XI Kikim Pasema Lahat. The sample in this study were all employees of the South Sumatra Provincial Forestry Service UPTD KPH Unit XI Kikim Pasema Lahat, totaling 37 employees. The sampling technique used is saturated sampling.The results showed that work facilities had a significant effect on the performance of the employees of the South Sumatra Provincial Forestry Service UPTD KPH Unit XI Kikim Pasema Lahat. Directions have a significant effect on the performance of the employees of the South Sumatra Provincial Forestry Service UPTD KPH Unit XI Kikim Pasema Lahat. Coordination has a significant effect on the performance of the Provincial Forestry Service of South Sumatra Province UPTD KPH Unit XI Kikim Pasema Lahat. Performance evaluation does not have a significant effect on the performance of the forest department employees of South Sumatra Province UPTD KPH Unit XI Kikim Pasema Lahat. Work facilities, direction, coordination and performance evaluation have a significant effect on the performance of the employees of the South Sumatra Provincial Forestry Service UPTD KPH Unit XI Kikim Pasema Lahat.